The role of accelerator stakeholders in young ventures’ business model innovations (BMI) - Hamani, Amina; Simon, Fanny (Management international / International Management / Gestiòn Internacional, 2023)
Although scholars recognize the need to integrate stakeholders into business model innovation (BMI), little research has been done on the link between stakeholders’ roles and young ventures’ BMI, particularly in the accelerator context. We addressed this research gap by conducting a longitudinal multi-case study in two corporate accelerators using semi-structured interviews, observations and documentation from young ventures’ perspective. Our results offer a more granular understanding of how different stakeholders enable the configuration of young ventures’ initial BM and spur BMI. Specifically, the study provides some original insights into accelerator ecosystems, networking activities and the contributions of both to young ventures’ BMI.